TIPOLOGI PENGUNJUNG DI KAWASAN WISATA HAPANASAN KABUPATEN ROKAN HULU - Nofyanti, Nur Afni; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Area of Hapanasan Rokan Hulu District is a one of attraction that as featured prodcut at Rokan Hulu distric and stregthed with governor’s decree and rokan hulu’s regent. Area of Hapanasan is area that has natural attractive with hot water in there as a superior product. But facilities that had been provided in there is not corresponding with visitor typologies in general that comes at there so that this area get reduction of visitors.This study aims to knowing general visitor typologies that come in area of Hapanasan Roka Hulu Disctrit, the visitor typhologis used theory by Smith there are explorer, elite, off-beat, unusual incipient mass, mass, charter.This study used quantitative method. This study use 100 respondens which a visitors that come at Hapanasan Rokan Hulu Distric as a respondents and doing interview with manager as a informan to completed. And then for determine of how many of all the respondens researcher use accidental sampling which reseacrcher take sampel with accidental which met accidental when the researcher at in Hapanasan Rokan Hulu Distric.This study identified into sevents main issues namely visitor thypologis viewed by Smith’s theory there are explorer, elite,off-beat, unusual, incipient mass, mass, charter. And then the researchers can know general visitor thypologist that come to Hapanasan area Rokan Hulu District.